Influencia de factores maternos, infantiles y domésticos en el manejo de la diarrea en Ecuador - VARGAS GAIBOR, KARLA VIOLETA (2024)
Background: Acute diarrheal disease is a leading cause of childhood morbidity and mortality worldwide, particularly among children under five years of age. Despite being a preventable and treatable condition, it remains a significant public health challenge. This study examines the complexities of acute diarrheal disease management in Ecuador, where geographic and socioeconomic diversity present unique health challenges. Objective: Using data from the 2018 National Health and Nutrition Survey (ENSANUT), the objective of this study was to examine the determinants of maternal approaches to diarrhea management in children under 5 years of age in Ecuador, focusing on how child, maternal, and household characteristics, including household size, urban-rural divide, sanitation facilities, socioeconomic factors such as poverty status, maternal education, and access to technology, and child-specific factors such as age, dehydration status, and ethnicity, influence the management of childhood diarrhea. Methods: This study used data from the 2018 Ecuadorian National Health and Nutrition Survey (ENSANUT) (1). Logistic regression models were used to assess the influence of different factors on diarrhea management practices. Results: The study found that maternal education level, maternal ethnic identification, maternal age, child age, urban or rural residence, and household size significantly influenced diarrhea management. Larger households were more likely to practice effective management. Children aged 0-11 months received less health care than children aged 19-23 months. However, factors such as child's birth order, child's gender, mother's marital status, and socioeconomic status were not significant predictors. Conclusions: This study highlights the complexity of acute diarrhea management in children under five years of age in Ecuador and how different socioeconomic, educational, cultural, and family factors influence home care practices. The results show that although most children receive some form of health care, significant disparities in disease management persist, particularly between urban and rural areas, and between different age and educational groups. Maternal education stands out as a key factor in the adoption of appropriate practices, while socioeconomic status was not found to be a significant determinant, which could be attributed to the coverage of the public health system in the country. In addition, family structure and cultural dynamics, such as the influence of other household members and traditional beliefs, may influence decisions about child health care.